The Reversible and Irreversible Phenomena in Potato Starch Gelatinization. (21st January 2019) - Skansberger, Tatyana; Kocherbitov, Vitaly
Abstract : Gelatinization of starch is a complex process and can be considered using two different approaches. In a kinetic approach it is considered as an irreversible process and described using the formalism of chemical kinetics with activation energy as the main parameter. Alternatively, in a thermodynamic approach it can be viewed as a reversible process with van't Hoff enthalpy as the main parameter. The experimental DSC data on gelatinization of native and physically modified potato starches presented in this study support the equilibrium approach. The van't Hoff enthalpy of gelatinization of native potato starch is measured to be 737 ± 13 kJ mol −1, and it is more sensitive to physical modifications of starch than the calorimetric enthalpy. Moreover, van't Hoff enthalpy has a clear correlation with the granule size, while neither gelatinization temperature, nor calorimetric enthalpy are sensitive to the size. To explain the nonequilibrium nature of starch gelatinization, the authors propose a three‐step mechanism, which includes reversible and irreversible steps. Abstract : Gelatinization of starch is a complex process that can be considered using either a kinetic (irreversible) or thermodynamic (reversible) approach. The experimental DSC data on gelatinization of native and physically modified potato starches presented in this study are consistent with the equilibrium thermodynamic approach. To take into account of the irreversible aspects of starch gelatinization, the authors suggest that gelatinization should be considered as a multistage process, which includes both reversible and irreversible steps.